Dose reduction techniques in coronary calcium scoring: the effect of iterative reconstruction combined with low tube voltage on calcium scores in a thoracic phantom - Vonder, Marleen; Meyer, Mathias; Henzler, Thomas (European journal of radiology, 2017)
Objectives: To define a dose-reduced coronary calcium CT protocol that provides similar calcium score values as a conventional 120kVp protocol. Methods: A thorax phantom containing 100 calcifications was scanned with the reference protocol (120kVp, 90 ref mAs, FBP) and 30 dose-reduced protocols (70-110kVp, 90 ref mAs, FBP and iterative reconstruction (IR) levels 1-5) with 3rd generation dual-source CT. For protocols that yielded similar detectability and calcium scores as the reference protocol, additional scans were acquired at reduced ref mAs. Kendall’s τb and independent-samples-median test were used to determine trends and differences in contrast/signal-to-noise ratio (CNR and SNR), dose and calcium scores. Results: The detectability and calcium scores decreased at increasing IR levels (τb<−0.825, p<0.001) and increasing tube voltage (τb<−0.679, p<0.001). For 90kVp-IR3 and 100kVp-IR1, similar detectability and calcium score was found compared to the reference protocol (p>0.206). For these protocols, lower tube currents did not affect the detectability and Agatston score (p>0.206), while CNR and SNR were similar/higher compared to the reference protocol (0.008<p<0.206). Dose reduction was 60.6% (90kVp-IR3) and 43.6% (100kVp-IR1). Conclusions: The protocol of 90kVp-IR3 and 100kVp-IR1 yielded similar calcium detectability, Agatston score and image quality as the reference protocol, with dose reduction up to 60.6%.